Jailed double-microcatheter technique following horizontal stenting for coil embolization of intracranial wide-necked bifurcation aneurysms: A technical report of two cases. Issue 2 (April 2017) - Kitahara, Takahiro; Hatano, Taketo; Hayase, Makoto; Hattori, Etsuko; Miyakoshi, Akinori; Nakamura, Takehiko
The horizontal stenting technique facilitates endovascular treatment of wide-necked bifurcation intracranial aneurysms. Previous literature shows, however, that subsequent coil embolization at initial treatment results in incomplete obliteration in many cases. The authors present two consecutive cases of wide-necked large bifurcation aneurysms to describe an additional coil embolization technique following horizontal stenting. The patients were a 53-year-old female with an unruptured internal carotid artery terminus aneurysm and a 57-year-old female with a recurrent basilar artery tip aneurysm. Both patients underwent endovascular treatment with horizontal stenting followed by coil embolization with jailed double-microcatheters. Immediate complete obliteration was achieved with no complications, and no recanalization was observed at the one-year follow-up in both cases. Coil embolization with jailed double-microcatheter technique following horizontal stenting is a safe and effective strategy for wide-necked bifurcation aneurysms.